The Condition of the Working Class: Representation and Praxis. Issue 4 (December 2013) - Wayne, Mike; O'Neill, Deirdre
<x xml:space="preserve">Abstract</x> This essay reflects critically on the political context, production process, ideas, and strategies of our feature‐length documentary film The Condition of the Working Class. It explores why we were inspired by Friedrich Engels' 1844 book of the same name and how that book connects with the contemporary neoliberal capitalist project that has dominated the political scene internationally for several decades. We conceptualize our film as a constellation, in the manner of Walter Benjamin, between the 1840s and the contemporary moment. The essay explores the production process of the film, which involved setting up and working in conjunction with a theatrical project. The essay reflects on the theatrical work of John McGrath and its connections with our own work. In the final section of the essay, the authors consider the finished film in more detail, analyzing how the film focused on the process of theatrical production and contextualized that process within wider spatial and temporal frames. The film and the theater project explore the possibility of reconstituting in a microcosm a working class collective subject that has been atomized and demonized by 30 years of neoliberal policy, which in the context of the present economic crisis seeks to drive its project even further.